Pengaruh Etos Kerja dan Lingkungan Kerja Terhadap Produktivitas Kerja Karyawan Perum Damri Cabang Lampung - Mila Rosanti; Hasbullah, Hasbullah; Dewi Silvia (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2023)
The aim of the research is to determine the influence of work ethic and work environment on the work productivity of Perum Damri Lampung Branch employees.  This type of research is quantitative, the population is all employees of Perum Damri Lampung Branch and the sample is 215 people.  The research results showed that there was an influence of work ethic on the work productivity of Perum Damri Lampung Branch employees.  The results of this research are supported by research conducted by Karimah (2017) and Lengkong (2020), explaining that partially work ethic has a significant influence on work productivity.  There is an influence of the work environment on the work productivity of Perum Damri Lampung employees.  The results of this research are supported by research conducted by Ningsih (2017) and Lengkong (2020), explaining that partially the work environment has a significant influence on work productivity.  There is an influence of work ethic and work environment on the work productivity of Perum Damri Lampung Branch employees.  The results of this research are supported by research conducted by Ningsih (2017) and Lengkong (2020), explaining that simultaneously work ethic and work environment have a significant influence on work productivity.